Laboratory Investigations for Bleeding Disorders - Hayward, Catherine P. M.; Moffat, Karen A.; Liu, Yang (Seminars in Thrombosis and Hemostasis, 2012)
Bleeding disorder panels often include the prothrombin time (PT)/international normalized ratio (INR), activated partial thromboplastin time (APTT), fibrinogen level, and thrombin time (TT). We explored the detection of abnormalities from bleeding disorders by these tests among subjects referred for bleeding disorder assessments, using data from a bleeding disorder study to determine sensitivities and specificities. Among subjects referred to hematologists for bleeding disorder assessment, coagulation defects were uncommon and the APTT and TT detected many nonsignificant abnormalities. While all test and panel specificities were acceptable (88 to 100%), coagulation screening tests were less sensitive to clinically significant abnormalities (1.0 to 2.1%) than von Willebrand disease (VWD) screens (6.7%), and light transmission platelet aggregometry (LTA) (26%). Accordingly, panels comprising PT/INR, APTT, fibrinogen, and TT had lower sensitivity to bleeding disorders (3.7%) than panels expanded to include VWD screens (8.5%), or VWD screens and LTA (30%). These findings have important implications for bleeding disorder diagnosis.
Keywords: bleeding disorders; laboratory testing; factor deficiencies; fibrinogen